Triage process for the assessment of coronavirus disease 2019‐positive patients with cancer: The ONCOVID prospective study. Issue 7 (3rd December 2020) - Indini, Alice; Cattaneo, Monica; Ghidini, Michele; Rijavec, Erika; Bareggi, Claudia; Galassi, Barbara; Gambini, Donatella; Ceriani, Rosalia; Ceriotti, Ferruccio; Berti, Emilio; Grossi, Francesco
Abstract : Background: Patients with cancer are considered at high risk for the novel respiratory illness coronavirus disease 2019 (COVID‐19). General measures to keep COVID‐19–free cancer divisions have been adopted worldwide. The objective of this study was to evaluate the efficacy of triage to identify COVID‐19 among patients with cancer. Methods: From March 20 to April 17, 2020, data were collected from patients who were treated or followed at the authors' institution in a prospective clinical trial. The primary endpoint was to estimate the cumulative incidence of COVID‐19–positive patients who were identified using a triage process through the aid of medical and patient questionnaires. Based on a diagnostic algorithm, patients with suspect symptoms underwent an infectious disease specialist's evaluation and a COVID‐19 swab. Serologic tests were proposed for patients who had symptoms or altered laboratory tests that did not fall into the diagnostic algorithm but were suspicious for COVID‐19. Results: Overall, 562 patients were enrolled. Six patients (1%) were diagnosed with COVID‐19, of whom 4 (67%) had the disease detected through telehealth triage, and 2 patients (33%) without suspect symptoms at triage had the disease detected later. Seventy‐one patients (13%) had suspect symptoms and/or altered laboratory tests that were not included in the diagnostic algorithm and, of these, 47 patients (73%) underwent testing for severe acute respiratory syndrome coronavirus 2 antibody: 6 (13%) were positive for IgG (n = 5) or for both IgM and IgG (n = 1), and antibody tests were negative in the remaining 41 patients. Conclusions: The triage process had a positive effect on the detection of COVID‐19 in patients with cancer. Telehealth triage was helpful in detecting suspect patients and to keep a COVID‐19–free cancer center. The overall incidence of COVID‐19 diagnosis (1%) and antibody positivity (13%) in patients with suspect symptoms was similar to that observed in the general population. Abstract : The adoption of a structured triage process can be useful for the detection of coronavirus disease 2019 symptoms and signs. Oncology activities can be safely carried out during the pandemic with the aid of a triage process and containment measures.